Groundwater uptake of different surface cover and its consequences in great Hungarian plain - Gribovszki Zoltán (ECOLOGICAL PROCESSES, 2017)
Forest cover in Hungary has increased from 1.1 to 2.0 million hectares during the last century. The EU (European Union) promotes further afforestation; thus, 15,000–18,000 ha are being forested each year, mainly in the Hungarian Great Plain. In terms of species used for afforestation, poplar plantations are preferred over native oak woodlands.